Analisis Kinerja Perusahaan Pertambangan Sub-Sektor Batu Bara Yang Terdaftar di Bursa Efek Indonesia (BEI) Pasca Perang Tarif (Trade War) Berdasarkan Laporan Tahunan Periode 2022-2024 - Yajid, Muh. Hasrul Yajid Baihaqi; Sasanti, Elin (Fakultas Ekonomi dan Bisnis Unram, 2025)
This study aims to analyze and compare the financial performance of coal sub-sector mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period, following the trade war between the United States and China. The conflict has triggered global economic uncertainty, affecting trade sectors, including the mining industry. This research employs a descriptive quantitative approach using secondary data from the annual reports of five coal mining companies : PT Bukit Asam Tbk, PT Adaro Energy Indonesia Tbk, PT Indo Tambangraya Megah Tbk, PT Bayan Resources Tbk, dan PT Bumi Resources Tbk. Financial performance was assessed using Current Ratio, Debt to Equity Ratio (DER), and Return on Equity (ROE). The results show that PT Indo Tambangraya Megah Tbk and PT Adaro Energy Indonesia Tbk demonstrated high levels of liquidity and solvency, while PT Bayan Resources Tbk recorded the highest profitability performance. Conversely, PT Bumi Resources Tbk exhibited the weakest financial position. This study provides valuable insights for investors and corporate management in formulating resilient financial strategies amid global economic pressures.